The impact of an enhanced health surveillance system for COVID-19 management in Serrana, Brazil - Natasha N. Ferreira; Pedro M.M. Garibaldi; Glenda R. Moraes; José C. Moura; Taline M. Klein; Larissa E. Machado; Lilian F.B. Scofoni; Simone K. Haddad; Rodrigo T. Calado; Dimas T. Covas; Benedito A.L. Fonseca; Ricardo Palacios; et al. (Elsevier, 2022)
Objective: To describe the successful implementation of an enhanced public health surveillance system based on early detection, tracing contacts, and patient follow-up and support. Study design: A prospective observational cohort study conducted in Serrana, São Paulo State, Brazil. Methods: The implementation was based on four axes: increasing the access to SARS-CoV-2 testing; correct swab collection; testing patients with mild symptoms; and patient follow-up. Positivity rate, patient demographic and clinical characteristics, dynamics of disease severity, SARS-CoV-2 genome evolution, and the impact on COVID-19 research were assessed from August 23, 2020 to February 6, 2021 (between epidemiological week 35/2020 and 5/2021, a total of 24 weeks). Results: The number of sites collecting rt-PCR for SARS-CoV-2 was increased from one to seven points and staff was trained in the correct use of personal protective equipment and in the swab collection technique. During the study period, 6728 samples were collected from 6155 participants vs. 2770 collections in a similar period before. SARS-CoV-2 RNA was detected in 1758 (26.1%) swabs vs. 1117 (36.7%) before the implementation of the surveillance system (p < 0.001). Positivity rates varied widely between epidemiological weeks 35/2020 and 5/2021 (IQR, 12.8%-31.3%). Out of COVID-19 patients, 91.1% were adults at a median age of 35 years (IQR, 25-50 years), 42.6% were men and 57.4% were women, with a SARS-CoV-2 positivity rate of 28.6% and 24.4% (p < 0.001), respectively. The most common symptoms were headache (72.6%), myalgia (65.0%), and cough (61.7%). Comorbidities were found in 20.8% of patients, the most common being hypertension and diabetes. According to the World Health Organization clinical progression scale, 93.5% of patients had mild disease, 1.6% were hospitalized with moderate disease, 3.2% were hospitalized with severe disease, and 1.4% died. The enhanced surveillance system led to the development of COVID-19 related research. Conclusions: The enhanced surveillance system in Serrana improved COVID-19 understanding and management. By integrating community and academic institutions, it was possible to monitor SARS-CoV-2 positive cases and variants, follow the epidemic trend, guide patients, and develop relevant research projects.